Cyclic Behaviour of Expanded Polystyrene (EPS) Sandwich Reinforced Concrete Walls - Ari Wibowo; Indradi Wijatmiko; Christin R. Nainggolan (Advances in Materials Science and Engineering, 2018)
Precast concrete walls become increasingly utilized due to the rapid needs of inexpensive fabricated house especially as traditional construction cost continues to climb, and also, particularly at damaged area due to natural disasters when the requirement of a lot of fast-constructed and cost-efficient houses are paramount. However, the performance of precast walls under lateral load such as earthquake or strong wind is still not comprehensively understood due to various types of reinforcements and connections. Additionally, the massive and solid wall elements also enlarge the building total weight and hence increase the impact of earthquake significantly. Therefore, the precast polystyrene-reinforced concrete walls which offer light weight and easy installment became the focus of this investigation. The laboratory test on two reinforced concrete wall specimens using EPS (expanded polystyrene) panel and wire mesh reinforcement has been conducted. Quasi-static load in the form of displacement controlled cyclic tests were undertaken until reaching peak load. At each discrete loading step, lateral load-deflection behaviour, crack propagation, and collapse mechanism were measured which then were compared with theoretical analysis. The findings showed that precast polystyrene-reinforced concrete walls gave considerable seismic performance for the low-to-moderate seismic region reaching up to 1% drift at 20% drop of peak load. However, it might not be sufficient for high seismic regions, at which double-panel wall type can be more suitable.